Effect of prednisolone on linear growth in children with nephrotic syndrome - Ehsan Valavi; Majid Aminzadeh; Parisa Amouri; Afshin Rezazadeh; Maedeh Beladi‐Mousavi (Brazilian Society of Pediatrics, 2020)
Objective: This study aims at determining the relationship between prednisolone cumulative dose and linear growth in pre‐pubertal children with idiopathic nephrotic syndrome. Method: This cross‐sectional study was conducted on all children with idiopathic nephrotic syndrome registered to the pediatric nephrology department at the main referral children's hospital in Southwestern Iran. Inclusion criteria included age (males <12 years; females <10 years), >6 months of use, and the minimum prednisolone cumulative dose of 152 mg/kg. The exclusion criteria were individuals who had entered puberty or had other diseases affecting linear growth. Based on the prednisolone cumulative dose of ≥550 mg/kg (four or more relapses), the children were divided into two groups. All data regarding age, height, and weight at disease onset and the last visit, bone age, and the parents' height were collected. Secondary variables including mid‐parental target height and predicted adult height were also calculated. Height data were compared between the different rates of relapse. Results: A total of 97 children (68% male) were enrolled. Their post-treatment mean height Z-score was less than that obtained before treatment (−0.584 vs. −0.158; p = 0.001). Subjects with higher prednisolone cumulative doses were found to have more reduction in height Z-score (p = 0.001). Post-treatment height prediction also showed less growth potential compared to pre-treatment target height (p = 0.006). Thirty-three children (34.4%) had four or more relapses, among whom more mean-height Z-score decreases were found compared to those with less-frequent relapses (−0.84 vs. −0.28; p = 0.04). Conclusion: This study showed the negative effect of cumulative dosages of prednisolone on linear growth, which was greater in children with four or more relapses. Resumo: Objetivo: Determinar a relação entre a dose cumulativa de prednisolona e o crescimento linear em crianças pré‐púberes com síndrome nefrótica idiopática. Método: Estudo transversal conduzido em todas as crianças com síndrome nefrótica idiopática registradas no departamento de nefrologia pediátrica no principal hospital infantil para encaminhamento no sudoeste do Irã. Os critérios de inclusão incluíram idade (meninos < 12 anos; meninas < 10 anos), > 6 meses e a dose cumulativa de prednisolona mínima de 152 mg/kg. Os critérios de exclusão foram indivíduos que entraram na puberdade ou tinham outras doenças que afetam o crescimento linear. Com base na dose cumulativa de prednisolona de ≥ 550 mg/kg (≥ 4 recidivas), as crianças foram divididas em dois grupos. Foram coletados todos os dados relacionados a idade, estatura e peso no início da doença e na última visita, idade óssea e estatura dos pais. Também foram calculadas as variáveis secundárias, inclusive estatura‐alvo e estatura adulta prevista. Os dados de estatura foram comparados entre as diferentes taxas de recidivas. Resultados: Foram inscritas 97 crianças (68% do sexo masculino). Seu escore z de estatura média pós‐tratamento foi inferior ao obtido antes do tratamento (−0,584 em comparação com −0,158; p = 0,001). Os indivíduos com maiores doses cumulativas de prednisolona mostraram maior redução no escore z para estatura (p = 0,001). A estatura pós‐tratamento também foi preditiva de menor potencial de crescimento em comparação com a estatura‐alvo pré‐tratamento (p = 0,006); 33 crianças (34,4%) apresentaram ≥ 4 recidivas, entre as quais foram encontradas mais reduções médias no escore z para estatura em comparação com as recidivas menos frequentes (−0,84 em comparação com −0,28; p = 0,04). Conclusão: Este estudo mostrou o efeito negativo das doses cumulativas de prednisolona sobre o crescimento linear, que foi maior em crianças com ≥ 4 recidivas. Keywords: Prednisolone, Linear growth, Children, Nephrotic syndrome, Palavras‐chave: Prednisolona, Crescimento linear, Crianças, Síndrome nefrótica